Management of Early Childhood Education (PAUD) in the Context of Improving The Quality of Learning in West Bandung Regency - Yulianti , Arfiani; Rusmini, Rusmini (The International Journal of Education Management and Sociology, 2023)
This research aims to compare the management of Early Childhood Education (PAUD), Integrated Pembina State, and Rabbi Rodiyyah Early Childhood Education, West Bandung Regency. These comparative aspects include comparisons of curriculum management, student management, teaching staff, infrastructure management, and financial management to improve the quality of learning at the two educational institutions. Data sources are teachers and students from both schools. Data collection techniques include observations at research locations at both institutions, mandala interviews with teachers and students, and documentation in the form of meeting notes, archives, and other literature to complement the data. This research method is comparative descriptive. The results of this research indicate that Early Childhood Education management. Rabbi Rodiyyah Early Childhood Education and Development, West Bandung Regency has many similarities and differences in several aspects that are mandatory to improve the quality of learning